Spontaneous Subcapsular Hepatic Haematoma: A Rare Case Report - Roisin Burrows-O’Donoghue; Rowena Donnison; Emmanuel D’Almeida (European Medical Journal, 2023)
A spontaneous subscapular hepatic haematoma is a rare condition that has not widely been reported in literature. Subscapular hepatic haematoma has a high mortality rate, especially if the haematoma ruptures, so early diagnosis is imperative. In this case report, the authors present an unusual case of subscapular hepatic haematoma of a female in her 70s, who, in her first few days of admission for the management of acute calculus cholecystitis, developed acute onset right upper quadrant and epigastric pain radiating to her back. Her haemoglobin dropped from 112 g/L to 54 g/L, and her liver function tests and coagulation studies became deranged. Abdominal and pelvic CT and angiography showed a subscapular liver haematoma without active bleeding. The patient received a blood transfusion and was managed conservatively, with no obvious cause being identified.